Gestão de serviços de saúde análise da qualidade dos sistemas de saúde público e suplementar do estado do Rio Grande do Sul - Marciano, Marcelo Antunes (Universidade do Vale do Rio dos Sinos, 2014)
This work examines how to improve quality in health services, both in the public system and in supplementary health, more specifically, in health insurance companies and hospitals in the state of Rio Grande do Sul (RS). The main goal of the present work is to improve quality for the public and supplementary health systems in the state of Rio Grande do Sul under the dynamic system they are included into. Specific goals are: Mapping the health system through systemic thinking, proposing points of leverage regarding the quality of the public health system in RS; and analyzing the compliance with the Managed Care criteria and innovation in health management by the players, namely, “health insurance companies” and “hospitals”. The work is composed of two articles, each delivering a specific goal, and by additional chapters that consolidate the delivery of the general goal. As for the methodological procedures, the research develops from a positivist paradigm and it is based on a qualitative perspective, making use of interviews, document analysis, secondary data collection in public-access databases, analysis based on multidisciplinary group dynamics assessment and modeling. As a result, this led to the creation of a map that highlights players and relations of this dynamic system, allowing for the identification of possible scenarios, points of leverage, and the suggestion of strategies to help improve the quality of the public health system in RS, as well as the awareness that contacted hospital players were found to be more compliant than the contacted health insurance companies as far as good management practices that guided this study are concerned. We argue that a integrated and standardized management system, which is systematically used, with the help of organizational strategies, innovation, and a focus on the value chain, takes into account assistance-related, economic, and competitive aspects of these players and, as a consequence, it may contribute to improve quality to services provided.
Keywords: Sistema de saúde pública; Gestão de operações de serviços de saúde; Melhoria da qualidade; Pensamento sistêmico; Inovação em gestão de saúde; Public health system; Health services operation management; Managed care; Quality improvement; Systemic thinking; Innovation in health management; ACCNPQ::Engenharias::Engenharia de Produção